2022
DOI: 10.3168/jds.2021-21173
|View full text |Cite
|
Sign up to set email alerts
|

Genomic prediction in Nordic Red dairy cattle considering breed origin of alleles

Abstract: This study investigated the reliability of genomic prediction (GP) using breed origin of alleles (BOA) approach in the Nordic Red (RDC) population, which has an admixed population structure. The RDC population consists of animals with varying degrees of genetic materials from the Danish Red (RDM), Swedish Red (SRB), Finnish Ayrshire (FAY), and Holstein (HOL) because bulls have been used across the breeds. The BOA approach was tested using 39,550 RDC animals in the reference population and 11,786 in the validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…The estimates of high correlations between the SNP effects of the breeds may occur for different reasons: i) there were five breeds combined in the OT group (beef and dairy breeds) which may lead to problems in assignments of alleles, ii) unassigned alleles were included in the OT group, iii) the imputation of genotypes was carried out jointly in a multi-breed setting for the entire population which might lead to errors in genotypes, and therefore in predictions using BOA. It has been shown that errors in assignments of alleles lead to an increase in the correlation of SNP effects between the breeds (Guillenea et al, 2022). Even with correlations higher than expected, the BOA model outperformed PBLUP but more importantly, also out-performed the SNP-BLUP model for animals of the Irish cattle population.…”
Section: Discussionmentioning
confidence: 93%
“…The estimates of high correlations between the SNP effects of the breeds may occur for different reasons: i) there were five breeds combined in the OT group (beef and dairy breeds) which may lead to problems in assignments of alleles, ii) unassigned alleles were included in the OT group, iii) the imputation of genotypes was carried out jointly in a multi-breed setting for the entire population which might lead to errors in genotypes, and therefore in predictions using BOA. It has been shown that errors in assignments of alleles lead to an increase in the correlation of SNP effects between the breeds (Guillenea et al, 2022). Even with correlations higher than expected, the BOA model outperformed PBLUP but more importantly, also out-performed the SNP-BLUP model for animals of the Irish cattle population.…”
Section: Discussionmentioning
confidence: 93%
“…However, when no crossbreds were in the training set, a BOA model did not outperform a model with combined training set of the 3 pure breeds without accounting for BOA. For empirical data, comparison of models with and without accounting for BOA for the admixed Nordic Red Dairy Cattle (RDC) populations did not show higher reliability from the BOA model (Guillenea et al, 2022). However, in that study, first, the pure subpopulations contributing to RDC were not clearly defined and had to be inferred from genotypes, and second, there were many generations of crossbreeding, which altogether made accurate detection of BOA difficult.…”
Section: Introductionmentioning
confidence: 79%
“…(2019) saw variable results as compared with a standard GBLUP. More generally, in stratified prediction, models that consider group effects (without specifically using a structured GBLUP framework) led to improvements in prediction accuracy (Guillenea et al., 2022; Karaman et al., 2021; Lyra et al., 2018; Ramstein & Casler, 2019). Here we show that a model developed for highly differentiated populations can improve prediction accuracy within a highly related population due to the presence of group‐specific marker effects associated with a large‐effect locus.…”
Section: Discussionmentioning
confidence: 99%
“…The marker effects may be estimated as the combination of two or more different marker effects, with one effect size per marker from each group of individuals carrying each large effect allele. Heterogeneity of marker effects has been established across diverse populations (Guillenea et al., 2022; Legarra et al., 2021; Lehermeier et al., 2015; Liu et al., 2011; Rio et al., 2020; Schulz‐Streeck et al., 2012; Veturi et al., 2019); however, no study has explored this possibility in the context of large‐effect loci in related populations. Common ways tested to increase prediction accuracy across populations have included stratified analysis or the addition of random group‐specific marker deviation terms to standard regression models (Lehermeier et al., 2015).…”
Section: Introductionmentioning
confidence: 99%